Preparation of microgel co-loaded with nuciferine and epigallocatechin-3-gallate for the regulation of lipid metabolism - Zhu, Shengnan; Xu, Weijia; Liu, Jun; Guan, Feng; Xu, Aichun; Zhao, Jin; Ge, Jian (Frontiers in Nutrition, 2022)
This study aims to enhance the stability and bioavailability of nuciferine (NF) and epigallocatechin-3-gallate (EGCG) by loading NF into liposomes and then incorporating the liposomes and EGCG into porous microgels (NFEG-microgel) prepared with chitosan and proanthocyanidin. Analysis of particle size (0.5–3.0 μm), electron microscopy, rheology, stability, and simulated gastrointestinal release confirmed that the prepared microgels had high encapsulation rate and good stability and release characteristics. Intervention experiments were performed by orally administering NFEG-microgel to high-fat diet rats to evaluate its efficacy and regulatory mechanism for blood lipid metabolism. NFEG-microgel intervention significantly reduced the body weight and serum lipid level, and the mechanism was related to the expression regulation of key genes involved in lipid metabolism and miRNAs (miR-126a-5p and miR-30b-5p) in serum extracellular vesicles. In addition, NFEG-microgel improved the diversity of gut microbiota by enriching short-chain fatty acids (SCFA)-producing bacteria and reducing harmful bacteria, suggesting that it can ameliorate lipid metabolism by regulating the intestinal flora community in rats.